Comparative study of performance of CMOS differential amplifier with different type of current sources - Raja Aris, Raja Siti Nur Adimah (2007)
In this work, the performance of Complementary Metal Oxide Semiconductor (CMOS) differential amplifier have been studied and analyzed based on AMI l.6µi technology using different load and different constant current sources. The constant current sources are designed based on total current equal to 200µA with W/L value of CMOS transistor being defined from the I-V characteristics curve. PSPICE simulator tools are used to simulate and verify the circuit. The higher the values of Common Mode Rejection Ratio (CMRR) will contribute to the best performance of the CMOS differential amplifier. From the simulation, it is found that differential amplifier with active load and Wilson current source has the best performance.